Glitz childhood: a study on the charges of beauty contests to children's bodies - Rafaela da Silva Melo; Rosangela de Fátima Rodrigues Soares (Universidade Federal de Santa Catarina, 2014)
From the excerpts of episodes of the reality show Toddlers and Tiaras and the contributions of childhood studies and post-structuralist theoretical perspective, I try to analyze the discourses of "truth" that support the need for radical transformation of children's bodies to meet the requirements of beauty contests. Discourses that have served as justification for contemporary forms of exploitation, abuse, discipline and government of infant bodies